Efficacy of liposomal amphotericin B eye drops at two concentrations in experimental aspergillus keratomycosis in rabbits - Husnun Amalia; Rahmawati Ridwan; Ari Estuningtyas; Ratna Sitompul; Robiatul Adawiyah; Hans-Joachim Freisleben (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Keratomycosis, a fungal corneal infection prevalent in tropical regions, frequently leads to visual impairment and blindness. Liposomal amphotericin B (L-AmB) offers improved efficacy and reduced toxicity compared to conventional amphotericin B deoxycholate and represents a promising option for topical ophthalmic use. Objective: To evaluate and compare the therapeutic efficacy of L-AmB eye drops at 0.15% and 0.5% concentrations in experimental Aspergillus keratomycosis in New Zealand White rabbits. Methods: Four rabbits received midstromal corneal inoculation with a mixed suspension of Aspergillus flavus, A. fumigatus, A. niger, and A. terreus (2 x 10⁴ CFU/0.05 mL). L-AmB eye drops were applied hourly from day 8 post-inoculation until corneal cultures became negative. Antifungal susceptibility was assessed by disc diffusion. Clinical response was monitored by slit lamp examination using a modified scoring system. Results: Negative corneal cultures were achieved in all treated eyes within 10 to 18 days (mean 15 days, L-AmB 0.15%) and 11 to 15 days (mean 14 days, L-AmB 0.5%). No toxic effects were observed. Complete corneal transparency without cicatrix was achieved in one eye treated with L-AmB 0.15%. Conclusion: Both concentrations were effective and safe. Liposomal AmB 0.15% appears as efficacious as 0.5% for experimental Aspergillus keratomycosis. Clinical studies in humans are warranted.